Investigation on surface roughness of ultrasonic assisted vapour smoothing of acrylonitrile butadiene styrene printed sample - Maidin, Shajahan; Rajendran, Thavinnesh Kumar; Sharum, Mohd Afiq; Mohd Norddin, Mohd Fitri; Ismail, Shafinaz; Kamarulnizam, Mohd (IOP Publishing Ltd, 2024)
Additive manufacturing offers many benefits, yet it is confronted with the challenge of rough surfaces resulting from the appearance of seam lines on the printed parts due to the layer-by-layer printing process. This study investigates the effect of ultrasonic-assisted vapor smoothing on the surface roughness of 3D-printed ABS samples. The ABS samples were printed with an open-source FDM printer. The vapour smoothing process was conducted by applying acetone and altering the ultrasonic frequencies and times to 0 kHz, 10 kHz, and 20 kHz for the frequencies and 10 min, 20 min, and 30 min for the times. The surface roughness measurements were performed using a Mitutoyo SJ-301 surface roughness tester. The findings demonstrated enhancements in the quality of the surface, reduction in the visibility of layer lines, and improved surface smoothness for all the samples. From the ANOVA analysis, the average value of Ra for 30 kHz frequency is 2.57 μm, which is better than 3.19 μm for 10 kHz frequency. The manipulation of ultrasonic frequencies and exposure durations decreased surface roughness parameters, suggesting enhancement of the time to attain smoother surfaces. This work demonstrates the effectiveness of ultrasonic-assisted vapour smoothing as a feasible post-processing technique for enhancing surface quality in 3D-printed ABS-printed parts.